Microalgae-bacterial granular systems able to treat marine aquaculture water streams - Alves, M. (2021)
This study aimed to evaluate the granulation of microalgae-bacterial biomass and its ability to treat marine aquaculture water streams. For this, a phototrophic consortium adapted to saline conditions was enriched from water collected from a marine aquaculture facility and then used to develop the microbial aggregates. Two lab-scale photo-reactors were used: one inoculated only with the enriched phototrophic consortium and the other with the consortium and activated sludge. Rapid granulation was achieved. High ammonium and organic carbon removals of about 100% and 80%, respectively, were quickly established and maintained in the long run. This study demonstrates the rapid granulation of phototrophic biomass and its robustness and feasibility for nutrient and carbon removal from extremely low loaded water streams.